Application of Apri and Fib_4 Biomarkers in Stratifying the Degree of Hepatic Involvement in HIV-HCV Coinfection - Serge Kouakou Kouassi; Doumbia Moussa; Alexis Bahi; Carole N’Guessan Djaman Obouayeba; Françis Adou Yapo; Joseph Allico Djaman (Advanced Concepts in Medicine and Medical Research Vol. 10, 2023)
HIV/Hepatitis C co-infections are common and represent major public health problems as it affects between 2 and 3 million people worldwide This study developed based onnon-invasive tests using biomarkers was conducted on patients co-infected with HIV and HCV. This chapter focuses on evaluating the degree of hepatic involvement using APRI and FIB 4 scores in liver damage in those co-infected with HIV/HCV in Côte d’Ivoire. This study qualitative method of semi-directive interviewing was used to interview that was conducted from September 2019 to November 2019Serological tests were performed to analyze the data. APRI and FIB 4 scores were calculated for each patient from biological data obtained by COBAS C311 (Roche Hitachi, Japan). Statistical analyses were performed using GraphPad and MED-CALC software. The study involved 30 patients (men) of middle age (25 - 52 years), with extremes ranging from 0.67 to 8 for APRI and 0.201 to 22 for FIB 4. A predictive APRI and FIB4 score of significant hepatic fibrosis was observed in 23% of patients; however, 46% and 54% of patients for the APRI and FIB 4 score, respectively, would not have significant fibrosis. An APRI and FIB4 score not included in the classification limits of the type of fibrosis hepatitis was observed in 31% and 23% of patients, respectively. The findings of this study revealed that APRI and FIB-4 good discriminatory capacity in the diagnosis of liver cirrhosis in people living with hepatitis C in accordance with other research. The study showed that APRI or FIB 4 score demonstrated good discriminatory capacity to classify patients into the different stages of liver fibrosis, as about 70 and 77%, respectively, of the patient population could be classified in the stages of hepatitis C fibrosis based on the interpretation of their criteria.